2018
DOI: 10.1111/apm.12786
|View full text |Cite
|
Sign up to set email alerts
|

Update on the pathology of gestational trophoblastic disease

Abstract: Gestational trophoblastic disease can be a challenging area for pathologic evaluation. An update with a focus on pathologic challenges is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…So, all the clinical, surgical, histological, and Immunohistochemical findings were compatible with a non-neoplastic trophoblastic disease, that is EPS. We did not think about it initially because it was not evident 19 . Our first clinical suspicion was about a submucosal leiomyoma, not consistent with the elevated serum levels of hCG.…”
Section: Discussionmentioning
confidence: 99%
“…So, all the clinical, surgical, histological, and Immunohistochemical findings were compatible with a non-neoplastic trophoblastic disease, that is EPS. We did not think about it initially because it was not evident 19 . Our first clinical suspicion was about a submucosal leiomyoma, not consistent with the elevated serum levels of hCG.…”
Section: Discussionmentioning
confidence: 99%
“…The second is a singleton triploid fetus with partial hydatidiform mole placenta (69 chromosomes, 23 maternal and 46 paternal) and the third is a twin gestation in which one fetus is diploid with normal placenta (46 chromosomes, 23 maternal and 23 paternal) and the other is triploid with partial hydatidiform mole placenta (69 chromosomes, 23 maternal and 46 paternal) (Matsui et al, 2000, Piura et al, 2008). In complete hydatidiform moles there is a lack of identifiable embryonic or fetal tissues and the chorionic villi exhibit generalized hydatidiform swelling and diffuse trophoblastic hyperplasia (Heller, 2018). Cytogenic studies have demonstrated that complete moles most commonly display a 46xx karyotype and molar chromosomes are entirely of paternal origin (Hoffner and Surti, 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the clinic, human chorionic gonadotrophin (hCG) is a diagnostic marker of choriocarcinoma as it is mainly produced by JEG-3 choriocarcinoma cells (Handschuh et al 2007, Fournier 2016). An increase in hCG concentration implies the advanced tumor stage and predictable metastasis in choriocarcinoma patients (Heller 2018). Despite the establishment of the etoposide, methotrexate, actinomycin, cyclophosphamide, vincristine (EMA/ CO) regimen as a conventional chemotherapeutic strategy against choriocarcinoma, 20-30% of high-risk patients do not respond to this regimen (Bower et al 1997).…”
Section: Introductionmentioning
confidence: 99%